Length-weight Relationship of Male and Female Sperata seenghala from River Gomti and River Saryu in Eastern Uttar Pradesh, India - Gautam, Abhishek; Saroj, Jyoti; Singh, C.P.; Patel, Puneet Kumar; Singh, Vipendra; Kumar, Rahul; Lavkush (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The present study, conducted from July 2023 to April 2024 at the College of Fisheries, Acharya Narendra Deva University of Agriculture and Technology, Kumarganj, Ayodhya, Uttar Pradesh, India, investigates the length-weight relationships (LWR) of Sperata seenghala from two major aquatic bodies in eastern Uttar Pradesh, the Gomti River (Site 1) and the Saryu River (Site 2). At Site 1, the LWR analysis revealed significant differences between males and females. Females exhibited a steeper slope than males, a difference statistically significant at the 1% level (p = 0.002312). The adjusted means between sexes did not show a significant difference (p = 0.082456). High R-squared values indicated a strong correlation between length and weight for both sexes, with males showing a slightly higher correlation (R² = 0.997015) compared to females (R² = 0.985104). Pooled data from Site 1 also demonstrated a robust correlation (R² = 0.995811), underscoring the strength of the LWR across sexes. At Site 2, the LWR analysis also indicated significant differences between males and females, with females having a slightly lower slope than males. This difference was statistically significant at the 5% level (p = 0.045766). Similar to Site 1, the adjusted means did not differ significantly (p = 0.104492). R-squared values confirmed a strong correlation between length and weight, with females showing a slightly higher correlation (R² = 0.99816) than males (R² = 0.990001). The pooled data from Site 2 further supported a robust LWR correlation (R² = 0.998624), indicating consistent growth patterns across sexes.